Cultural Global Hegemony and Globalization: Hollywood’s LGBTQ+ Impacts in Asian Film Industry - Mutiara Tsabitah; Nathanael Jusac Lie; Rizqi Magdawati Nur Izzizti (Soshum: Jurnal Sosial dan Humaniora, 2022)
It is indisputable that globalization provides a vast space for various aspects of the world to continue developing and connecting. Through this, culture, as one of the aspects most affected by the times and technological advances, is the main focus of hegemonic companies such as Hollywood to expand their work, especially in cinema. This paper attempts to explain the impact of globalization on cultural hegemony in Asian countries due to the widespread influence of the film industry from Hollywood, especially the LGBTQ+ genre. The film industry in Asia has undergone many transformations over time since the impact of Hollywood's hegemony. Asia itself is a country that carries a very different culture from Western culture. This paper then explains this phenomenon using a qualitative research method based on observation of case studies per country, such as Japan, South Korea, and Indonesia. Through this method, this paper has concluded how the influence of American Culture through its film industry as a form of dominant culture has affected the film industry in Asia (Japan, Korea, and Indonesia). Thus, providing arguments of similarities in the elements of LGBTQ+ by films produced by Hollywood and the film industry in Asia.